Immunotherapy in multiple myeloma: advances from immune microenvironment insights to clinical application - Yao Zhang; Yuting Lei; Yanzhao Huang; Yan Gao; Rong Liu; Kaiyun Guo; Chunlian Zhao; Ming Lei (Molecular Biology Reports, 2026)

Aging of buried polyvinyl chloride sewer pipes and microplastics release: Mechanisms and environmental risks - Yuanling Luo; Yuting Ding; Xiya Ao; Xiaoxi Liao; Haiyin Xu; Yin Zhang; Ming Huang; Meiying Jia; Xinjiang Hu; Min Ruan; Erping Li; Jia Yang (Journal of Environmental Chemical Engineering, 2026)

A ratiometric fluorescent probe with distinct response to Aflatoxin B1 and B2a: probe design, bioimaging, and quantification - Linhui Peng; Yuting Luo; Zhiqing Xun; Zhongyong Xu; Taoyuze Lv; Xinrong Du; Zhaohui Wang; Ya-Long Wang; Tianyi Qin; Bin Liu; Ming-Qiang Zhu (Food Chemistry, 2026)

Low-dose PFOS exposure exacerbates rheumatoid arthritis via SIRT2–PAD4–mediated macrophage pyroptosis - Zeqing Sun; Linghui Yu; Yun Li; Haoran Guo; Mengyao Li; Yuting Wen; Shasha Yao; Qiuju Liang; Zhijie Xu; Jiaqi Zhang; Ming Yang; Sijin Liu; et al. (Journal of Hazardous Materials, 2026)

Inhibitory effects of polyethylene, polylactic acid microplastics and tyre wear particles on soil nitrification via decreasing ammonium availability and altering microbial communities - Surui Ji; Xuanqi Zhang; Yawen Li; Yuting Zhang; Bin Shao; Jin Liu; Ming Zeng (Journal of Soils and Sediments, 2026)

Molecular simulation of CO₂ enhanced recovery and storage in organic-inorganic composite nanopores of shale gas reservoirs - Fengming Gong; Dali Hou; Zhiqiang Lei; Jin Liu; Chunming Pan; Yuting Ming (Chemical Engineering Journal, 2026)

Light-at-night exposure drives myopia via melanopsin signalling - Jiaxin Li; Congying Li; Meijun Wang; Jianjun Meng; Jiajia Dang; Ying Huang; Di Shi; Xinyu Li; Shan Cai; Tianli Peng; Yunfei Liu; Yuting Kang; et al. (Science China Life Sciences, 2026)

Metabolomic profiling reveals activity-correlated chemotypes and strain-specific metabolites in mangrove-derived actinomycetes - Bonan Yan; Ming Chen; Ling Li; Peixi Zhang; Ki Shi; Li Guo; Yixin Tang; Chunlan Li; Yanjun Di; Chen Zhu; Yuting Wu; Chenlei Lian; et al. (Natural Product Research, 2026)

M2 macrophage-derived apoptotic extracellular vesicles mediate immune reprogramming and inhibit osteoclastogensis via mitophagy to ameliorate periodontitis - Jiahua Li; Tianyao Wang; Xueting Zhao; Yuting Chen; Xu Chen; Kai Zheng; Ming Zhang; Huiqing Gou; Yan Xu (Chemical Engineering Journal, 2026)

Mono(2-ethylhexyl) phthalate activates JNK signaling via TLR4-MD2 binding to induce podocyte injury in chronic kidney disease - Jiajun Jing; Shaohui Liu; Li Yan; Li'e Zhang; Qiuju Liang; Yuting Wen; Xiaofeng Huang; Zijuan Qi; Mingjun Wang; Zi'ang Huang; Sijin Liu; Yunfeng Zou; et al. (Journal of Hazardous Materials, 2026)

ROS responsive polydopamine coated black phosphorus nanocarrier for enhanced methylprednisolone delivery in acute lung injury immunotherapy - Zhiwei Gao; Mengxue Mo; Qianyue Liu; Jiaxiao Li; Hongshuai Zheng; Yaohui Huang; Yan Liu; Jing Qian; Xuzhi Liang; Yuting Xiao; Yan Long; Chen Qian; et al. (Chemical Engineering Journal, 2026)

Corrigendum to “Effect of Flammulina velutipes polysaccharides on the quality and digestibility of fresh wet rice noodles: A study perspective from physicochemical and postprandial glucose homeostasis in vivo” [Food Chem. 484 (2025) 144335] - Tingting Bu; Xiao Kong; Yuting Ren; Zhiguo Zhang; Weiwei Hu; Komarova Natallia; Ming Cai; Peilong Sun; Weicheng Wu; Kai Yang (Food Chemistry, 2025)

Three birds, one-stone strategy for efficient removal of organic pollutants using trifunctional iron porphyrin polymer - Miao Hu; Di Hao; Zhengyang Song; Wei Zhu; Tingyang Ming; Yuting Xu; Boyu Wang; Qing Li (Journal of Environmental Chemical Engineering, 2025)

GNSS spoofing detection based on lightweight features and CGAN-ANN in unknown scenarios - Lichao Chen; Xiaofeng Ouyang; Fangling Zeng; Zixuan Rui; Yuting Ming (GPS Solutions, 2025)

Effect of Flammulina velutipes polysaccharidees on the quality and digestibility of fresh wet rice noodles: A study perspective from physicochemical and postprandial glucose homeostasis in vivo - Tingting Bu; Xiao Kong; Yuting Ren; Zhiguo Zhang; Weiwei Hu; Komarova Natallia; Ming Cai; Peilong Sun; Weicheng Wu; Kai Yang (Food Chemistry, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

An integrated framework for wildfire emergency response and post-fire debris flow prediction: a case study from the wildfire event on 20 April 2021 in Mianning, Sichuan, China - Yao Tang; Yuting Luo; Lijuan Wang; Ming Chen (Natural Hazards, 2025)

Migrasome-related ITGA5 for predicting prognosis, immune infiltration and drug sensitivity of hepatocellular carcinoma - Wanjin Chen; Kailin Liu; Zhiling Wang; Hui Zhang; Ming Tan; Yuting Liu; Tingting Gao; Xiameng Su; Leirong Gu; Xinyan Chen; Shengtao Cheng (Apoptosis, 2025)

Polarized microenvironment-modulated covalent organic frameworks with nickel single atoms for enhanced CO2 photoreduction - Piyan Wang; Yingchen Dai; Zisheng Song; Yan Wang; Jingru Wei; Zhijie Liu; Yuting Ma; Fengyi Yang; Jiafu Qu; Shuzhi Liu; Yahui Cai; Xiaogang Yang; et al. (Chemical Engineering Journal, 2025)

Quantifying the effects of aerosols and cloud radiative effect on rice growth and yield - Yuting Liu; Lunche Wang; Xinxin Chen; Zigeng Niu; Ming Zhang; Jia Sun; Junfang Zhao (Agricultural and Forest Meteorology, 2025)

Mechanisms and river blocking effects of clustering debris flows on 20 August 2019 along the Minjiang River, Wenchuan, China - Yuting Luo; Ming Chen; Lijuan Wang; Yao Tang; Song Ma (Journal of Earth System Science, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Exploring the immunomodulatory mechanisms of Osmunda japonica Thunb polysaccharides: Activation of MAPK and NF-κB signaling pathways - Xiaochen Liu; Rui Xu; Yuting Miao; Yining Zang; Yuxin Huang; Yuying Zheng; Fengwei Li; Ming Wei; Rui Xiao; Xiaohong Yu (Food Bioscience, 2025)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Natural background levels, source apportionment and health risks of potentially toxic elements in groundwater of highly urbanized area - Yunhui Zhang; Yuting Yan; Rongwen Yao; Denghui Wei; Xun Huang; Ming Luo; Changli Wei; Si Chen; Chang Yang (Science of The Total Environment, 2024)

Recent developments of single atom alloy catalysts for electrocatalytic hydrogenation reactions - Zehua Jin; Yuting Xu; Manjeet Chhetri; Julia Wood; Brian Torreon; Fanglin Che; Ming Yang (Chemical Engineering Journal, 2024)

Effect of two different Flammulina velutipes polysaccharides on the physicochemical and digestive properties of rice starch and their interaction mechanisms - Tingting Bu; Yuting Ren; Yue Yu; Weicheng Wu; Zhiguo Zhang; Weiwei Hu; Jun Lu; Jian Wang; Ming Cai; Kai Yang; Peilong Sun (Food Bioscience, 2024)

Effects of High-Water Fluoride Exposure on IQ Levels in School-Age Children: A Cross-Sectional Study in Jiangsu, China - Yuting Xia; Yan Xu; Ming Shi; Song Liu; Suwan Liu; Hui Wang; Chaoyong Dai; Yunjie Ye; Mao Liu; Li Shang; Yang Wang; Peihua Wang (Exposure and Health, 2024)

Groundwater suitability assessment for irrigation and drinking purposes by integrating spatial analysis, machine learning, water quality index, and health risk model - Yuting Yan; Yunhui Zhang; Rongwen Yao; Changli Wei; Ming Luo; Chang Yang; Si Chen; Xun Huang (Environmental Science and Pollution Research, 2024)

Quantitative assessment of expected direct economic losses of buildings for debris flows in multiple rainfall intensity scenarios in Yangling Gully, Southwest China - Ming Chen; Yuting Luo; Chuan Tang; Ning Li (Natural Hazards, 2024)

Cobalt-loaded carbon nanofibers as magnetic catalyst for tetracycline degradation through peroxydisulfate activation: Non-radical dominated mechanism - Yifan Wang; Xiaoxuan Kang; Yuting Li; Ruyi Li; Chang Wu; Luyao Wang; Chongqing Wang; Tao Yang; Ming Ge; Zhangxing He (Journal of Water Process Engineering, 2024)

Development of nucleic acid extraction and real-time recombinase polymerase amplification (RPA) assay integrated microfluidic biosensor for multiplex detection of foodborne bacteria - Yuting Shang; Gaowa Xing; Haifeng Lin; Yucheng Sun; Shulang Chen; Jin-Ming Lin (Food Control, 2024)

Association between ADAMTS14_rs4747096 gene polymorphism and bone mineral density of Chinese Han population residing in fluorine exposed areas in ShanXi Province, China - Ming Qin; Yue Gao; Meichen Zhang; Junhua Wu; Yang Liu; Yuting Jiang; Xiaodi Zhang; Xin Wang; Yanmei Yang; Yanhui Gao (Environmental Science and Pollution Research, 2023)

Simultaneous and rapid screening of live and dead E. coli O157:H7 with three signal outputs: An all-in-one biosensor using phage-apoferritin@CuO2 signal tags on MXenes-modified electrode platform - Shu Xiao; Cong Cao; Tinghong Ming; Yuting Cao; Zhenzhong Yu; Ning Gan (Journal of Hazardous Materials, 2023)

Oxidative pretreatment of refractory gold ore using persulfate under ultrasound for efficient leaching of gold by a novel eco-friendly lixiviant: Demonstration of the effect of particle size and economic benefits - Qihao Gui; Likang Fu; Yuting Hu; Haokai Di; Ming Liang; Shixing Wang; Libo Zhang; Enhua Dong (Hydrometallurgy, 2023)

Implications for biological invasion of non‐native plants for sale in the world's largest online market - Achyut Kumar Banerjee; Tien Ming Lee; Hui Feng; Xinru Liang; Yuting Lin; Jiakai Wang; Minghui Yin; Hao Peng; Yelin Huang (Conservation Biology, 2023)
Internet trade is increasingly recognized as a dispersal pathway of non‐native plant species that is difficult to monitor. We sought to identify non‐native flora present in the Chinese online market, the largest e‐commerce market globally, and to decipher the effect of existing trade regulations, among other variables, on e‐trading patterns and to inform policy. We used a comprehensive list of 811 non‐native plant species in China present in 1 of the 3 phases of the invasion continuum (i.e., introduced, naturalized, and invasive). The price, propagule types, and quantities of the species offered for sale were retrieved from 9 online stores, including 2 of the largest platforms. Over 30% of the non‐native species were offered for sale in the online marketplaces; invasive non‐native species dominated the list (45.53%). No significant price difference was observed across the non‐native species of the 3 invasion categories. Among the 5 propagule types, a significantly higher number of non‐native species were offered for sale as seeds. The regression models and path analyses consistently revealed a direct positive effect of the number of uses and species’ minimum residence time and an indirect effect of biogeography on the pattern of trade in non‐native plant species when minimal phylogenetic signal was detected. A review of the existing phytosanitary regulations in China revealed their inadequacy in managing e‐trading of non‐native plant species. To address the problem, we propose integration of a standardized risk assessment framework that considers perceptions of stakeholders and is adaptable based on continuous surveillance of the trade network. If implemented successfully, the measures could provide a template for other countries to strengthen trading regulations for non‐native plant species and take proactive management measures.

Correction to: Remote effect of model systematic bias in tropical SST on the cold bias over the Tibetan Plateau - Yuting Wu; Xiaoming Hu; Zhenning Li; Ming Cai; Mengmeng Lu; Song Yang (Climate Dynamics, 2023)

Remote effect of model systematic bias in tropical SST on the cold bias over the Tibetan Plateau - Yuting Wu; Xiaoming Hu; Zhenning Li; Ming Cai; Mengmeng Lu; Song Yang (Climate Dynamics, 2023)
Most state-of-the-art climate models substantially underestimate the near-surface air temperature (SAT) over the Tibetan Plateau (TP), especially for the cold season. While previous studies have attributed this cold bias to local factors such as the elevation difference, coarse resolution, and excessive snow cover, this investigation addresses the potential contributions of the systematic bias of tropical sea surface temperature (SST) to the TP cold bias. Experiments with the NCAR Community Atmosphere Model demonstrate that tropical SST bias results in an apparent cold bias over the TP, especially in boreal winter, and explains about 40% of the deviation in multi-model mean SAT over the TP relative to station observations. Forced by the tropical SST bias, heat flux exhibits an anomalous divergence over the plateau, causing a cooling center in the mid- and lower-troposphere over the TP. This atmospheric cooling in turn leads to a reduction of the downward longwave radiative fluxes reaching the surface, less energy supply, and thus a cold bias over the TP.

Which strategy among avoid, shift, or improve is the best to reduce CO2 emissions from sand and gravel aggregate transportation? - Yuting Zhu; Hao Ma; Chuan Sha; Yang Yang; Haijiao Sun; Feifei Ming (Journal of Cleaner Production, 2023)

Gold extraction using alternatives to cyanide: Ultrasonic reinforcement and its leaching kinetics - Qihao Gui; Likang Fu; Yuting Hu; Haokai Di; Ming Liang; Shixing Wang; Libo Zhang (Minerals Engineering, 2023)

The role of meteorological factors in suicide mortality in Wuhu, a humid city along the Yangtze River in Eastern China - Lingxiang Yu; Tingting Zhou; Ming Shao; Tao Zhang; Jinian Wang; Yubo Ma; Shanshan Xu; Yuting Chen; Jiansheng Zhu; Faming Pan (Environmental Science and Pollution Research, 2022)

Proteomic analysis of coarse and fine skin tissues of Liaoning cashmere goat - Zhixian Bai; Yanan Xu; Ming Gu; Weidong Cai; Yu Zhang; Yuting Qin; Rui Chen; Yinggang Sun; Yanzhi Wu; Zeying Wang (Functional & Integrative Genomics, 2022)

Scleractinian diversity in the upper mesophotic zone of Ludao (Taiwan): a museum collection with new records from Taiwanese waters - Stéphane De Palmas; Vianney Denis; Derek Soto; Yuting Vicky Lin; Ming-Jay Ho; Chaolun Allen Chen (Marine Biodiversity, 2021)

Establishment and characterization of an immortalized human chondrocyte cell line - Jiashu Yang; Yuting Tang; Wensun Chen; Ming Zhang; Fangling Hong; Dawei Yang; Qianyi Bao; Ying Yang; Yucui Jin; Lingyun Li; Changyan Ma (Biotechnology Letters, 2020)

Development and utilization of functional KASP markers to improve rice eating and cooking quality through MAS breeding - Guili Yang; Siping Chen; Likai Chen; Weiwei Gao; Yuting Huang; Cuihong Huang; Danhua Zhou; Jiafeng Wang; Yongzhu Liu; Ming Huang; Wuming Xiao; Hui Wang; et al. (Euphytica, 2019)

Effects and mechanisms of meta-sodium silicate amendments on lead uptake and accumulation by rice - Mingliu Zhao; Yuting Liu; Honghong Li; Yifan Cai; Ming Kuang Wang; Yanhui Chen; Tuanhui Xie; Guo Wang (Environmental Science and Pollution Research, 2017)

In Vivo Exposure of Kaempferol Is Driven by Phase II Metabolic Enzymes and Efflux Transporters - Liang Zheng; Lijun Zhu; Min Zhao; Jian Shi; Yuhuan Li; Jia Yu; Huangyu Jiang; Jinjun Wu; Yunli Tong; Yuting Liu; Ming Hu; Linlin Lu; et al. (The AAPS Journal, 2016)